Cross-Cultural analysis of Managerial and Cultural Values in Russia and China - K. Choi; D. D. Kochetkova (Управленческие науки)
The subject of the study is the differences in managerial and cultural values that are important for mutual understanding and interaction between Russia and China, countries with significant influence on the world economy and international relations. The study is particularly relevant in the context of business negotiations and management, where respect for values and beliefs inherent in other cultures is critical to successful cooperation. The purpose of this analysis is to examine the methods of G. Hofstede, R. Lewis, P. Ghemawat and others in the field of cultural differences and to compare their findings and conclusions with the results of a survey of Russian managers to verify the cultural characteristics contained in the literature and to prove their viability in practice. The results of the work confirmed the conclusions made by the above-mentioned academicians. The authors of the study defined the Russian culture as multi-active, highlighting the similarities and differences between the cultures of Russia and China. In both countries, the younger generation prioritizes personal career goals and financial success, which significantly changes the work process in terms of shifting values and orientations. The findings could provide valuable information for businesses and policymakers in these countries. The need to identify the cultural characteristics of Chinese managers and to better understand the cultural differences between Russia and China necessitates further research.